2020
DOI: 10.1177/0162353220912010
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs About Human Intelligence in a Sample of Teachers and Nonteachers

Abstract: Research in educational psychology consistently finds a relationship between intelligence and academic performance. However, in recent decades, educational fields, including gifted education, have resisted intelligence research, and there are some experts who argue that intelligence tests should not be used in identifying giftedness. Hoping to better understand this resistance to intelligence research, we created a survey of beliefs about intelligence and administered it online to a sample of the general publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 76 publications
4
24
2
Order By: Relevance
“…Although there is research regarding beliefs about giftedness and intelligence, only one research study posited the intersection of the two. Warne and Burton (2020) surveyed teachers’ and the general public’s views of intelligence and found that empirically unsupported viewpoints are very common. Thus, understanding the perceptions of teachers about intelligence and giftedness requires culture-specific or cross-cultural research because such perceptions are culturally bound.…”
Section: Cultural Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is research regarding beliefs about giftedness and intelligence, only one research study posited the intersection of the two. Warne and Burton (2020) surveyed teachers’ and the general public’s views of intelligence and found that empirically unsupported viewpoints are very common. Thus, understanding the perceptions of teachers about intelligence and giftedness requires culture-specific or cross-cultural research because such perceptions are culturally bound.…”
Section: Cultural Contextmentioning
confidence: 99%
“…Warne and Burton (2020) claimed that some reports in textbooks focus more on controversies over intelligence than consistent research evidence. Some of the basic findings and theories on intelligence have been de-emphasized in favor of egalitarian viewpoints.…”
Section: Cultural Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The crux of the matter is that intelligence has radically different meanings to different people. Most notably, there is a perceptible difference in understanding of this construct between those who conduct research on intelligence and lay people (Limeri et al, 2020;Warne & Burton, 2020). Where researchers who study intelligence tend to see intelligence as a relatively stable construct measuring cognitive abilities (Deary, 2014;Warne, 2020; since the work of Spearman, 1904Spearman, /1961, lay people are more likely to conflate intelligence with knowledge (Limeri et al, 2020) or hold a view of intelligence that is more consistent with Gardner's theory of multiple intelligences (Warne & Burton, 2020).…”
Section: What Is Intelligence Anyway?mentioning
confidence: 99%
“…In the real detection stage of 3D objects in power grid equipment, in view of the changes in the warehouse environment and the diversity of models and other factors, we put forward a new neural network-based 3D object detection method in combination with YOLOV3 and MobileNet model, realized efficient and robust 3D object detection, combined with real-world rendering technology [9] , enhanced the generalization ability of the algorithm, and further ensured the detection results through edge-based optimization technology. Finally, compared with other methods on the LineMod dataset, the feasibility of the proposed algorithm is verified.…”
Section: Future Application Prospects and Technological Improvementsmentioning
confidence: 99%